Association between the triglyceride-glucose index and hyperuricemia in patients with type 2 diabetes mellitus - Sun, Xu; Li, Xin; Qian, Zhuyin; Chen, Xiaowei; Zhang, Jie; Zhao, Chenjian; Liu, Xingyu (Frontiers in Endocrinology, 2025)
AimThis cross-sectional study investigated the relationship between the triglyceride-glucose (TyG: A surrogate marker for assessing insulin resistance.) index and hyperuricemia (HUA: Metabolic diseases caused by purine metabolism disorders.) risk in Chinese patients with type 2 diabetes mellitus (T2DM).MethodsFrom January 2021 to December 2023, T2DM patients were enrolled from Luhe District People’s Hospital in Nanjing. Participants were stratified by TyG index quartiles. Logistic regression and restricted cubic spline (RCS) analyses assessed the TyG-HUA association.ResultsThis study included 996 participants with type 2 diabetes, with a male predominance of 54.82%, a mean age of 60.39 years, and a median TyG index of 7.63. Compared to the lowest TyG quartile, the highest quartile exhibited a 4.23-fold (95% CI: 1.46 ~ 12.24, P value = 0.008) increased HUA risk. Restricted cubic spline analysis revealed a nonlinear relationship between the TyG index and HUA (nonlinear P value = 0.044). As the TyG level increased, the risk of HUA initially rose and then showed a downward trend (P for TyG = 0.008).ConclusionsElevated TyG index independently predicts HUA risk in T2DM patients. Early metabolic intervention may mitigate HUA-related cardiovascular morbidity and mortality.